Estudio de factibilidad de una empresa de ladrillos ecológicos de alta densidad - Mancheno Saá, Marcelo Javier (2014)
1.Introducción. --2.Marco Teórico. --3.Metodología. --4.Propuesta. --5.Bibliografía. --6.Anexos.